Nortriptyline Enhances Morphine-Conditioned Place Preference in Neuropathic Rats: Role of the Central Noradrenergic System. (September 2017) - Mi, Wenli; Wang, Shuxing; You, Zerong; Lim, Grewo; McCabe, Michael F.; Kim, Hyangin; Chen, Lucy; Mao, Jianren
Abstract : BACKGROUND: Combination drug therapy is commonly used to treat chronic pain conditions such as neuropathic pain, and antidepressant is often used together with opioid analgesics. While rewarding is an intrinsic property of opioid analgesics, it is unknown whether the use of an antidepressant would influence opioid reward, which may contribute to opioid addiction. In this study, we examined whether nortriptyline (a tricyclic antidepressant and a first-line medication for neuropathic pain) would enhance the morphine rewarding property in both naive and chronic constriction sciatic nerve injury (CCI) rats. METHODS: The rewarding effect of these drugs was assessed using conditioned place preference (CPP). The real-time polymerase chain reaction, western blot, and enzyme-linked immunosorbent assay analysis were used to investigate the function of central noradrenergic system. RESULTS: In naive rats, coadministration of nortriptyline with morphine did not change the acquisition of morphine-induced CPP. However, nortriptyline enhanced the acquisition, delayed the extinction, and augmented the reinstatement of morphine-induced CPP in CCI rats. In CCI rats treated with both nortriptyline and morphine, the expression of α2A-adrenergic receptors, norepinephrine transporter, and tyrosine hydroxylase was markedly decreased in the locus coeruleus, whereas the norepinephrine concentration in the nucleus accumbens was remarkably increased. CONCLUSIONS: These results demonstrate that nortriptyline enhanced morphine reward when both drugs were used to treat neuropathic pain in rats and that this behavioral phenotype is likely to be mediated by upregulation of the central noradrenergic system. These findings may have implications in opioid therapy commonly used for chronic pain management. Abstract : Published ahead of print May 19, 2017.